2015
DOI: 10.1093/schbul/sbv132
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Ownership and Endorsement of “mHealth” Among People With Psychosis: A Meta-analysis of Cross-sectional Studies

Abstract: There is currently growing interest in using mobile phones to support the treatment of psychotic disorders, such as schizophrenia. However, the widespread implementation of these interventions will ultimately depend upon patients' access to mobile devices and their willingness to engage with mobile health ("mHealth"). Thus, we conducted a systematic review and meta-analysis to assess mobile phone ownership and interest in mHealth among patients with psychosis. An electronic search of Ovid MEDLINE, Embase, Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
268
8
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 344 publications
(298 citation statements)
references
References 42 publications
18
268
8
4
Order By: Relevance
“…These results contradict the lower rates obtained by the NAMI study in 2014 [7], and they are more similar to the results of recent studies [9,11,18], which found that the access and use of technology in patients diagnosed with psychotic disorders are equivalent to those in the general population. The differences between the two comparison groups in our study suggested that the access and use are not equivalent between FEP and CP patients.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…These results contradict the lower rates obtained by the NAMI study in 2014 [7], and they are more similar to the results of recent studies [9,11,18], which found that the access and use of technology in patients diagnosed with psychotic disorders are equivalent to those in the general population. The differences between the two comparison groups in our study suggested that the access and use are not equivalent between FEP and CP patients.…”
Section: Discussioncontrasting
confidence: 74%
“…Based on these studies, we elaborated the survey, which is divided into five parts: the items for the first part, which aims to assess clinical and demographic information and the items for the second part, which measures the access and use of the internet, mobile and social media, were taken from the Spanish National Statistic Institute (INE) survey and from Trefflich et al [10] and Robotham et al [16] studies. Items for the third part of the questionnaire, which assesses the use of the internet in relation to mental health, and the items for the fourth part, which measures experiences with technology and the effect of internet usage on patient's health, were based on a survey of the National Alliance on Mental Illness (NAMI) [7] and the studies of Firth et al [9] and Gay et al [11]. The last part of the survey, which rates the interest of the patients in using an e-Health app and their interest in different tracking and reminder services, was an originally developed section.…”
Section: Methods: Measures and Designmentioning
confidence: 99%
See 3 more Smart Citations